Case Request On-line - Jón Heiðar Erlendsson 1979-; Ragnar Ómarsson 1984- (2014)
This report covers in detail a B.Sc. project at Reykjavík University in fall 2014. This project is conducted in a collaboration with a software company named Annata. Annata develops resource management solutions for various fields within the automotive industry. The goal of this project is to develop an extension for Annata IDMS, which allows individuals to book service appointments themselves on-line for their vehicle.